Impact of Long Working Hours on Family Life in Korea - Shun Wang (Korea Development Institute (KDI), 2015)
Korea is well known for its long working hours amongst employees, being always no. 1 or 2 in OECD ranking for average annual hours. Researchers find that the long working hours have detrimental effects on productivity and employees' material well-being such as work-related injuries and illness. However, it's less explored how the long working hours affect the subjective well-being of employees and their children. In this regard, Professor Wang of KDI School of Public Policy and Management studies the impacts of employees' working hours on their quality of life, measured by subjective well-being indicators. Professor Wang exploits a nationally representative longitudinal data, the Korean Labor and Income Panel Study (KLIPS) 1998-2012, to conduct the empirical analysis. The study can increase the understanding of workers' subjective well-being and then shed some light on the labor regulations in Korea.
Keywords: 330